PEMBUATAN MESIN PAHAT PELUBANG STATIS UNTUK INDIUSTRI KECIL MEBEL KA YU - Darmono, Darmono (Universitas Negeri Yogyakarta, 2005)
A voucher program of manufacturing a static hole-making wood- .chiseling machine for small-scale industrial companies producing wooden furniture was conducted with the objective of increasing the productivity of the wooden furniture production company of Indah Jaya in especially mak ing holes for joint construction in the furniture produced. Another objective was to determine the capacity and productivity of the machine itself.The program was conducted through the stages of planning the ma chine, manufacturing it, and training company workers in operating it. The planning stage covered the steps of drafting a design of the machine, calcu lating the materials for its manufacture, and estimating the cost of the manu facture. The manufacturing stage covered the steps of cutting the materials according to the design in the draft, welding some parts together, assem bling all the components into a unit, installing electrical appliances in it, testing its performance in operation, and painting it. The training stage co vered the steps of delivering a lecture on its theoretical aspects, demonstrat ing its operation, and giving company workers practice in operating it.The program has resulted in the actualization of a static hole-makingwood-chiseling machine and in company workers' acquisition of skills in operating it. With a round iron frame 10 em in diameter combined with a wooden frame 6 cm by 12 ern in size, making it 120 ern by 100 em by 50 em in its dimensions, and powered by an SEM electrical motor generator of12HP and rotation speed of 2800 RPM, in its performance and productivity at making holes of the same form and size in wood the machine has been five to eight times faster than manual tools.Keywords: hole-making machine, small-scale woodfurniture industry